2018
DOI: 10.1017/s0950268817002953
|View full text |Cite|
|
Sign up to set email alerts
|

Online market research panel members as controls in case–control studies to investigate gastrointestinal disease outbreaks: early experiences and lessons learnt from the UK

Abstract: Established methods of recruiting population controls for case–control studies to investigate gastrointestinal disease outbreaks can be time consuming, resulting in delays in identifying the source or vehicle of infection. After an initial evaluation of using online market research panel members as controls in a case–control study to investigate a Salmonella outbreak in 2013, this method was applied in four further studies in the UK between 2014 and 2016. We used data from all five studies and interviews with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…A number of methods have been proposed in the past that include comparing cases against different types of information for ‘controls’ such as market research panels using online questionnaires [31, 32], case-case study designs [14, 33, 34] and a simulation-type approach for generating ‘control’ information [35]. An attempt has been made in the Netherlands to collect background population exposure via an infectious disease repeated electronic survey that can then be used in outbreak investigations [36].…”
Section: Discussionmentioning
confidence: 99%
“…A number of methods have been proposed in the past that include comparing cases against different types of information for ‘controls’ such as market research panels using online questionnaires [31, 32], case-case study designs [14, 33, 34] and a simulation-type approach for generating ‘control’ information [35]. An attempt has been made in the Netherlands to collect background population exposure via an infectious disease repeated electronic survey that can then be used in outbreak investigations [36].…”
Section: Discussionmentioning
confidence: 99%
“…This paper presents the results of a novel comparison between food exposure data from market panel recruited controls and an established population survey. This is an important comparison given the increasing use of these approaches in outbreak investigation in the UK and internationally [ 17 ]. We found that when adjusted for socio-demographic factors, there were statistically significant differences in the percentage of participants exposed to 90% of foods between both panels and the reference data; however, in the context of large ORs typically associated with foodborne exposures leading to outbreaks the difference was practically important (a greater than threefold difference in odds of reported exposure) for only 11% of foods.…”
Section: Discussionmentioning
confidence: 99%
“…Issues previously identified with using market research panels include panel responsiveness, socio-demographic representativeness, careless responses, overlap between panel membership and biases due to recruitment [ 29 , 30 ], though market research companies attempt to address these issues through routine practice [ 17 ]. One of the key benefits of this approach, however, is the efficiency with which large numbers of controls can be rapidly recruited with little public health resource [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online market research panel members as controls in case-control studies to investigate gastrointestinal disease outbreaks: early experiences and lessons learnt from the UK -ERRATUM P. Mook One of the authors of the above article (Mook, P, et al (2018)), affiliations were incorrectly identified in the original article. They have been correctly listed below:…”
mentioning
confidence: 99%